The Role of Technology in Educational Resource Management: A Literature Review of Current Trends - Banjarnahor, Lampita; Gustiani, Frisca; Barus, Inneda Citra; Pulungan, Lilik Hidayat (Lembaga Riset Mutiara Akbar, 2024)
The aim of this research is to clarify the role of technology in managing educational resources. Educational resources have undergone many changes since the beginning of the digital era. The digital era has had a major impact on the way educational institutions recruit, train and motivate digital era teachers and educational staff. Rapidly developing technology has an impact on every aspect of human life. Technology has made work easier, increased productivity, and opened up new opportunities for institutions to develop faster. The results of this research reveal that the role of technology in managing educational resources plays a very influential role in education. In writing this article, we used a library review method where researchers collected research-related materials from books, magazines, scientific works., literature, mass media reports, etc., then describe and explain the data